COMPARATIVE STUDY OF EXHAUST EMISSIONS DIESEL FUELED SHIPS AND LIQUEFIED NATURAL GAS (LNG) - henny pasandang nari (Jurnal Maritim Malahayati, 2023)
LNG can be used as an alternative fuel in the shipping industry and as ship fuel because it can reduce exhaust emissions from CO2 by 30%, NOx by 85%, and SOx by 99.9% or 100%. If using Heavy Fuel Oil (HFO), the exhaust emissions cannot be reduced or equal to 100%. NOx emission restrictions, SOx are regulated in Maritime Pollution (MARPOL) Annex VI, in the future IMO will limit SOx gas emissions in fuel. Ships that will pass through Emissions Control Areas must limit sulfur in their fuel to 0.10%. Thus, LNG as an environmentally friendly fuel can be used in the ECA area.This study aims to calculate the amount of CO2, SOx, and NOx composition that can be reduced by using LNG. The method used is a literature study by recording technical data and ship operational data as primary data and other references from books, papers, journals, internet as secondary data. The ship data contains power, rotation, cylinder diameter, piston stroke, and other data needed to calculate the amount of CO2, SOx, and NOx composition that can be reduced if using LNG.The results showed that exhaust gas emissions CO2, SOx, and NOx that can be reduced by 25.2%, 100% and 79.46%.